Connecting to learn : educational and assistive technology for people with disabilities - Scherer, Marcia J. (Marcia Joslyn), 1948- (Washington, DC : American Psychological Association, 2004)
(from the jacket) This book is a comprehensive approach to matching the right assistive technology with students with disabilities, especially visual and auditory disabilities. The author explores the way disabilities, especially those involving the senses, can lead to isolation and a lack of "connectedness," and how this leads to educational difficulties. A step-by-step model for assessing and evaluating the needs of individual students and finding the right assistive technology to hep each student, is provided. This book features data on prevalence of vision and hearing loss as well as quotations from students and teachers about the various technologies they use in their schools and in daily life.
Foreword
Preface
Acknowledgments
Introduction
* The fundamental sense of connectedness / Marcia J. Scherer / 3-20
Learner characteristics and preferences
* The effects of loss of hearing or vision on the learner and learning / Marcia J. Scherer / 23-55
* The personal meaning of hearing or vision loss / Marcia J. Scherer / 41-55
Environments for learning
* The move from separate to inclusive education / Marcia J. Scherer / 59-71
* Contrasting inclusive with exclusive education / Marcia J. Scherer / 73-89
* Technology made inclusive education possible / Marcia J. Scherer / 91-106
Technologies for access to information and for instructional delivery
* Computers: Mixing assistive, information, and access technologies / Marcia J. Scherer / 109-123
* Desirable and less desirable effects of educational technologies / Marcia J. Scherer / 125-145
* Getting going on learning / Marcia J. Scherer / 147-158
Matching learners with the most appropriate technologies and strategies for their use
* Individual learner preferences and needs / Marcia J. Scherer / 161-181
* The matching person and technology model / Marcia J. Scherer / 183-201
Connecting to learn
* Bringing it all together for the individual user / Marcia J. Scherer / 205-259
Appendix A: Matching person and technology process and samples of the assessment forms
Appendix B: Copy of statement of need form
Appendix C: Checklists for educational technology evaluation and selection
Finding and funding assistive technologies
Appendix E: Resources
Glossary
References
Author index
Subject index
About the author
Includes bibliographical references (p. 265-280) and indexes.
Keywords: People with disabilities -- Education -- United States; People with disabilities -- United States -- Computer-assisted instruction; Self-help devices for people with disabilities -- United States; Assistive listening systems -- United States; edukacijske tehnologije; osobe s posebnim potrebama